Analysis of Factors Affecting Foreign Direct Investment (FDI) Inflows in Indonesia - Yuniarto, Agung (Universitas Muhammadiyah Magelang, 2020)
ABSTRACT This study aims to examine the factors that influence the inflow of Foreign Direct Investment (FDI) in Indonesia. The data in this study are panel data that combines time series data and cross sectional data. Time series data covers the period 1990 to 2018, while cross sectional data covers partner countries that hold tax treaty with Indonesia. The research hypothesis was tested with panel data regression. Based on the results of the analysis, it is obtained evidence that the Tax Treaty (Perjanjian Penghindaran Pajak Berganda/P3B) variable has different effects based on its age range. Tax treaty which has a short-term age range has no effect on FDI inflow, medium age range has a negative effect, and a long-term range has a positive effect. Therefore the government can maximize the flow of FDI from countries that have a long-term tax treaty life span. Openness in trade in partner countries also has a positive effect on FDI inflows in Indonesia (FDI). The higher level of trade openness with partner countries, means the lower trade barriers in the country. Whereas the ratio of GDP per capita of partner countries to Indonesia and the exchange rates of partner countries to USD negatively affect FDI inflows.